Remue-méninges dans les sciences du genre, Entretien avec Rebecca Jordan-Young - Mozziconacci, Vanina (Emulations - Revue de sciences sociales, 2018)
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; corps; cours; discipline; discours dominant; europe; france; inégalités; premier cycle; pédagogie; périodes historiques; racisme; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; états-unis

“I can never be too comfortable”: Race, gender, and emotion at the Hospital Bedside - Cottingham, Marci D.; Johnson, Austin H.; Erickson, Rebecca J. (Qualitative Health Research, 2018)
In this article, we examine how race and gender shape nurses’ emotion practice. Based on audio diaries collected from 48 nurses within two Midwestern hospital systems in the United States, we illustrate the disproportionate emotional labor that emerges among women nurses of color in the white institutional space of American health care. In this environment, women of color experience an emotional double shift as a result of negotiating patient, coworker, and supervisor interactions. In confronting racist encounters, nurses of color in our sample experience additional job-related stress, must perform disproportionate amounts of emotional labor, and experience depleted emotional resources that negatively influence patient care. Methodologically, the study extends prior research by using audio diaries collected from a racially diverse sample to capture emotion as a situationally emergent and complex feature of nursing practice. We also extend research on nursing by tracing both the sources and consequences of unequal emotion practices for nurse well-being and patient care.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; infirmières; intersectionnalité; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; sexisme; systèmes d'oppressions; systèmes hospitaliers; thématiques; travail; travail émotionnel; états-unis

Trente - Darsigny, Marie (Les éditions du remue-ménage, 2018)
Trente, un nombre qui n’arrivera jamais et s’il arrive, je l’éviterai, comme j’ai une fois évité un chevreuil en conduisant sur la route, le chevreuil courait devant mon auto, à gauche il y avait la rivière et à droite il y avait le fossé, c’est beau la Montérégie, au lieu de choisir l’un ou l’autre il continuait d’avancer droit devant, puis il a fini par bondir vers le fossé. Moi j’aurais choisi l’eau et d’ailleurs, à chaque fois que j’empruntais ce chemin-là, ça me chicotait de savoir que juste un petit coup de volant pouvait m’envoyer dans la rivière, un jour on est en vie et un jour on ne l’est plus, c’est tout.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; corps; cours; discours dominant; fem3500; féminisme pop; premier cycle; périodes historiques; québec; régions géographiques; santé; sexisme; systèmes d'oppressions; thématiques; violences

Climate change, colonialism, and women’s well-being in Canada: What is to be done? - Williams, Lewis (Canadian Journal of Public Health, 2018)
The impacts of accelerating climate change across Canada are unequally distributed between populations and regions. Emerging evidence shows climate change and resultant policies to be worsening gendered social and economic inequities between women and men, with women’s participation largely absent in climate change research and decision-making. These dynamics are resulting in negative impacts for women’s well-being, with Indigenous and historically marginalized women at increased risk of experiencing health inequities as a result of climate change. To date, public health discourse has largely failed to incorporate gender as a key determinant of health in discussions of climate change impacts on populations. Paralleling this lack of development, the entangled relationship between climate and colonialism tends to be subsumed under the term “Aboriginality” within health determinants discourse. This commentary on gender and climate change in Canada is framed within a radical intersectional approach as an alternative course of public health analysis and action aimed at addressing resulting health and power inequities. Following an overview of evidence regarding the gendered impacts of climate change on women’s work, roles, agency, and well-being, several possible public health action areas on climate change and gender are highlighted as necessary components for resilient communities capable of meeting contemporary challenges.
Keywords: amériques; approches et analyses; canada; changements climatiques; environnement; intersectionnalité; invisibilisation des femmes autochtones; projet charge mentale; régions géographiques; santé; santé des femmes*; sexisme; système colonial; systèmes d'oppressions; thématiques